Lassa Fever Infection among Healthcare Workers during the 2018 Outbreak in Nigeria - Ogbaini-Emovon, Ephraim; Erah, Francis; Osagiede, Emmanuel Friday; Nnadi, Chinelo Juliana; Ogbetere, Yemihan; Tobin, Ekaete A.; Asogun, Danny; Okonofua, Martha; Akpede, George; Akhideno, Peter; et al. (International Journal of Occupational Safety and Health, 2023)
Introduction: Healthcare workers (HCWs) are potentially exposed to infection during viral hemorrhagic fever outbreaks. In the wake of 2018, Nigeria experienced an unprecedented surge in cases of Lassa fever (LF), which affected HCWs. To guide infection prevention and control (IPC) strategies in similar settings, we characterize HCWs' infection and describe the gaps in IPC standards and practices during the outbreak. Methods: Data was collected using a structured questionnaire, interview, and review of case notes of 21 HCW with laboratory-confirmed Lassa fever who were treated at the Irrua Specialist Teaching Hospital (ISTH) Irrua and the Alex-Ekwemen Federal Teaching Hospital, Abakaliki (AEFETHA), between 1st January and 27th May 2018. Information collected was the patients' socio-demographic characteristics, date of potential exposure and onset of illness, nature, and type of exposure, clinical features, outcome, use of personal protective equipment (PPE), and personnel IPC training and were analyzed using descriptive statistics with Microsoft Excel. Results: The study included 21 HCWs, and 12 (57.14%) were doctors. The case fatality rate was 23%. Nearly two-thirds (62%) of the HCWs could describe a likely procedure leading to their exposure and infection. Among 13 HCWs, 85% had multiple blood and body fluids exposure, while 15% had needle stick injury or scalpel cut. About one-fifth of the participants had received some IPC training. Conclusion: Limited IPC adherence and inappropriate risk assessment were identified as factors leading to Lassa fever exposure and infection among HCWs. There is an urgent need to provide IPC training for all HCWs and to ensure an adequate supply of IPC materials to all healthcare facilities as part of emergency preparedness, especially in LF endemic areas.